ART EDUCATION BASED ON LOCAL WISDOM - Triyanto Triyanto (Proceeding of International Conference on Art, Language, and Culture, 2017)
Education as a cultural process is an effort to humanize and civilize people. Through education,individuals transfer, inherit and transmit knowledge, values, and beliefs that function as guides to fulfilling human needs in local contexts. The educational process occurs across generations through socialization, enculturation, and internalization. In this regard, education can be carried out through formal, non-formal, and informal ways. This paper argues the importance of preserving and cultivating local wisdom that is a form of culture containing knowledge, values, and beliefs that can benefit society. More specifically, this paper discusses that art education as a form of education that utilizes art as its medium has a strategic role in preserving and cultivating local wisdom.